The Millennial Generation is Pancasila on Social Media - Fina Puspa Effendi; Dinie Anggraeni Dewi (Institut Pendidikan Indonesia, 2021)
This research aims to ensure that the millennial generation uses social media well and implements Pancasila values ​​on social media. This research uses a qualitative research method or descriptive approach, where the theoretical basis is obtained from the literature, books, journals, the internet and other media. We are already in the digital era, where this era has led to the digitalization of all areas, the way of social life that was previously conventional has become digital, one of which is the way of socializing. Pancasila is currently being tested by the rise of hoax news such as social politics and SARA. For this reason, as a millennial generation emerging in the midst of the digital era, they must be aware of technology and use social media well. Social media also provides opportunities for the millennial generation to implement Pancasila values ​​through various social media platforms. By adhering to the values ​​of Pancasila, the state's position is guaranteed and national integration remains strong.